The Role of Collagen I, Magnesium and Phosphorus in Iraqi Meningioma Patients - Rasha Zuhair Jasim (Iraqi Journal of Pharmaceutical Sciences, 2024)
Meningiomas are the most common primary intracellular slow growing benign tumor that are mostly arisen from meningeothelial (arachnoid) cells which surround the brain and the spinal cord. The aim of the present study is to innovate a biochemical relationship between collagen I and meningiomas in Iraqi patients and also to examine the biochemical role of magnesium and phosphorus regarding this complex nervous disease. Thirty (30) diagnosed meningioma patients were participated in the present study and were classified into two (2) groups : G3 composed of (15) newly diagnosed meningioma males and G4 composed of (15) newly diagnosed meningioma females , both G3 and G4 subjects did not take any treatment linked with meningioma or any chronic disease. Patients groups were compared with healthy subjects as two control groups which did not suffer from any chronic disease , the first G1 composed of (15) healthy males and the second G2 composed of (15) healthy females in the range of age matched with patients groups. Blood samples were collected from each subject enrolled in this study and three biochemical parameters (collagen I , magnesium , phosphorus ) were determined in sera of all groups. Results of the present study have reported that levels of collagen I , magnesium and phosphorus were highly significant decreased in sera of G3 and G4 compared with G1 and G2 respectively , while the difference between G3 and G4 was non significant for the three biochemical parameters. The present study has contributed to collagen I novelty regarding Iraqi patients with meningiomas deficiency and also highlighted the biochemical role of both magnesium and phosphorus in accordance with meningiomas. The present study recommends checking periodically the levels of collagen I , magnesium and phosphorous by laboratory tests and treatment with collagen supplements tablets and metabolics ( magnesium phosphate ) capsules if a deficeicy has been noticed. .………………